2021
DOI: 10.3390/cells10081891
|View full text |Cite
|
Sign up to set email alerts
|

The Immune System Throws Its Traps: Cells and Their Extracellular Traps in Disease and Protection

Abstract: The first formal description of the microbicidal activity of extracellular traps (ETs) containing DNA occurred in neutrophils in 2004. Since then, ETs have been identified in different populations of cells involved in both innate and adaptive immune responses. Much of the knowledge has been obtained from in vitro or ex vivo studies; however, in vivo evaluations in experimental models and human biological materials have corroborated some of the results obtained. Two types of ETs have been described—suicidal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 205 publications
(435 reference statements)
0
27
0
Order By: Relevance
“…Fátima Conceição-Silva et al [44] have shown that neutrophils, macrophages, lymphocytes, eosinophils, basophils, and mast cells can produce extracellular traps (ET), even if the modalities are still not completely known. Patients with severe cases of COVID-19 are predisposed to thrombosis in which ETs produced by neutrophils may participate.…”
Section: Basophils and Covid-19 Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Fátima Conceição-Silva et al [44] have shown that neutrophils, macrophages, lymphocytes, eosinophils, basophils, and mast cells can produce extracellular traps (ET), even if the modalities are still not completely known. Patients with severe cases of COVID-19 are predisposed to thrombosis in which ETs produced by neutrophils may participate.…”
Section: Basophils and Covid-19 Diseasementioning
confidence: 99%
“…Mast cells are ubiquitous in the body, and they are involved in several conditions including viral infections, systemic inflammatory diseases, asthma, neuroinflammatory diseases, traumatic brain injury, stroke, and several stress disorders [44,56].…”
Section: Basophils and Covid-19 Diseasementioning
confidence: 99%
“…Over the last years, many studies linked the process of NETosis to oncogenic transformation, angiogenesis, cancer development and metastasis ( 19 , 20 ). In different pathological contexts (thromboinflammation, atherosclerosis, systemic lupus erythematosus, infection, sepsis), it became also evident that other blood, immune and specialized cells could also generate extracellular traps (ETs) ( 21 , 22 ). In this review, we provide a detailed analysis of extracellular DNA function in cancer and also discuss the different sources and origins of ETs and provide the hypotheses on their possible impact on tumor cells and tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…In the first scenario, mtDNA is first released into the cytosol, and then is enclosed in vesicles that fuse with the cell membrane, leading to mtDNA extrusion. An alternative possibility is that a fusion of mitochondrial and cell membrane occurs, leading to the release of mitochondrial content, including mtDNA, in the extracellular space [ 100 ].…”
Section: Mechanisms Of Release Of Mtdna In Biological Fluidsmentioning
confidence: 99%